The fauna of aquatic invertebrates of the Western Bug River - Moroz, Michail D.; Baitchorov, Vladimir M.; Giginiak, Juriyi G. (Experimental Biology and Biotechnology, 2019)
Тhe species composition and abundance of aquatic invertebrates in the river the Western Bug River in the vicinity of Brest were studied. 70 species of macrozoobenthos and pleiston complexes belonging to 3 orders of invertebrate animals: Mollusca – 23; Annelida – 4; Arthropoda – 43 species and forms were registered. A large number of groups of species that are rheophilic properties is an important ecological feature of the studied ecosystem and, obviously, specifies the high quality of waters in the studied river. Among the identified aquatic invertebrates of greatest interest is the discovery of rare and protected species – dragonflies Ophiogomphus cecilia (Fourcroy, 1785) and mayflies Ametropus fragilis Albarda, 1878. The larvae of these amphibiotic insect species show rheophilic and oxyphilic properties.
Keywords: waterways; taxonomical structure; rare species; the protected and invasive species; Belarus